MINIMALISASI MINIMUM ZONE CIRCLE MENGGUNAKAN METODE STATIONARY POINT - Oktriadi, Yudi; Saputra, Anggi; Kurniawan, Zaldy; Wahyudie, Ilham Ary (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2025)
The success of the manufacturing world in improving production processes is greatly influenced by the machine equipment used. SKD-11 steel has high wear resistance and good ductility, so it is suitable for components that require high precision and durability. Surface Response Method (RSM) Box-Behnken Design can be used in the optimization process, which has three variables that can predict the best optimum value. The roundness variable used in this research is MZC (Minimum Zone Circle), whose non-roundness value is the difference between the radius of the most extensive circle profile and the smallest circle profile, MZC. From the test results, it was found that the smallest non-sphericity was 7.5 μm. The optimal value for this test is VC 234.784 m/minute, feeding 0.127 mm/rev and depth of cut 0.18 mm, and the predicted response value is 13.05 μm. From the results of the ANOVA analysis, these three factors have no effect on roundness, but there is one factor that almost influences roundness, namely the depth of cut.